Insights into the development of microbial fuel cells for generating biohydrogen, bioelectricity, and treating wastewater. (1st September 2022) - Ahmed, Shams Forruque; Mofijur, M.; Islam, Nafisa; Parisa, Tahlil Ahmed; Rafa, Nazifa; Bokhari, Awais; Klemeš, Jiří Jaromír; Indra Mahlia, Teuku Meurah
Abstract: Bio-electrochemical systems, such as microbial fuel cells (MFCs), serve as greener alternatives to conventional fuel energy. Despite the burgeoning review works on MFCs, comprehensive discussions are lacking on MFC designs and applications. This review paper provides insights into MFC applications, substrates used in MFC and the various design, technological, and chemical factors affecting MFC performance. MFCs have demonstrated efficacy in wastewater treatment of at least 50% and up to 98%. MFCs have been reported to produce ∼30 W/m 2 electricity and ∼1 m 3 /d of biohydrogen, depending on the design and feedstock. Electricity generation rates of up to 5.04 mW/m −2 –3.6 mW/m −2, 75–513 mW/m −2, and 135.4 mW/m −2 have been found for SCMFCs, double chamber MFCs, and stacked MFCs with the highest being produced by the single/hybrid single-chamber type using microalgae. Hybrid MFCs may emerge as financially promising technologies worth investigating due to their low operational costs, integrating low-cost proton exchange membranes such as PVA-Nafion-borosilicate, and electrodes made of natural materials, carbon, metal, and ceramic. MFCs are mostly used in laboratories due to their low power output and the difficulties in assessing the economic feasibility of the technology. The MFCs can generate incomes of as much as $2, 498.77 × 10 −2 /(W/m 2 ) annually through wastewater treatment and energy generation alone. The field application of MFC technology is also narrow due to its microbiological, electrochemical, and technological limitations, exacerbated by the gap in knowledge between laboratory and commercial-scale applications. Further research into novel and economically feasible electrode and membrane materials, the improvement of electrogenicity of the microbes used, and the potential of hybrid MFCs will provide opportunities to launch MFCs from the laboratory to the commercial-scale as a bid to improve the global energy security in an eco-friendly way. Graphical abstract: Image 1 Highlights: MFCs, serve as greener alternatives to conventional fuel energy. 30 days of MFC operation can yield up to 10.38 mA current and remove 94.3% of COD by bacterial strains. MFCs are capable of generating ∼30 W/m2 of electricity and ∼1 m 3 /d of biohydrogen. MFCs have a wastewater treatment efficacy of at least 50% and up to 98%. MFC technology is narrow due to its microbiological, electrochemical, and technological limitations.